MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) TERHADAP PENINGKATAN HASIL BELAJAR EKONOMI SISWA KELAS X DI SMA NEGERI 1 KAWANGKOAN - Dame, Joubert M.; Lempas, Jety D.; Makaliwe, Niny; Mandome, Deslin (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This research aims to determine the effect of the application of the Problem Based Learning (PBL) learning model on the economic learning outcomes of class X students of SMA Negeri 1 Kawangkoan. This research method uses the Experiment method with a Pretest-Posttest Control Group Design, using a research sample of 71 students in class X where the XE class is an experimental class with a total of 36 students and the XD class is a control class with a total of 35 students with the sample technique used is Simple Random Sampling. The results of the study show that the Problem Based Learning learning model has an effect on the economic learning outcomes of class X students. This is shown by the results of the posttest of the t-test where the t-count > t-table is 3.89 > 1.67 so that H0 is rejected and H1 is accepted. This means that there is an influence of the Problem Based Learning learning model on students' economic learning outcomes. This value is strengthened by the mean posttest of the learning outcomes of the experimental class (80.42) higher than that of the control class (73.14), thus showing that the experimental class is better than the control class. Keywords: Problem Based Learning (PBL) Learning Model, Learning Outcomes Economics